Flora & Ulysses : the illuminated adventures - DiCamillo, Kate; Campbell, K. G. (Keith Gordon), 1966- (Somerville, Massachusetts : Candlewick Press, 2013)
Rescuing a squirrel after an accident involving a vacuum cleaner, comic-reading cynic Flora Belle Buckman is astonished when the squirrel, Ulysses, demonstrates astonishing powers of strength and flight after being revived.
KVBA 2014-2015.
Newbery Medal, 2014
Keywords: Squirrels -- Juvenile fiction; Superheroes -- Juvenile fiction; Humorous stories